Evaluation of periodontal status and cytokine levels in saliva and gingival crevicular fluid of patients with inflammatory bowel diseases. Issue 11 (19th July 2022) - Enver, Ayaz; Ozmeric, Nurdan; Isler, Sila Cagri; Toruner, Murat; Fidan, Cigdem; Demirci, Gulsah; Elgun, Serenay; Silva, Andre Paes B. da
Abstract: Background: Periodontal diseases and inflammatory bowel diseases (IBD, ulcerative colitis [UC] and Crohn disease [CD]) have been reported to present with increased salivary and gingival crevicular fluid (GCF) concentrations of cytokines. The aim of this study was to evaluate the salivary and GCF levels of TNF‐α, IL‐1β, IL‐10, and IL‐17A and their associations with the periodontal statuses of UC, CD, and non‐IBD patients, and to analyze the interrelationships among these cytokines, IBD conditions, and periodontal diseases. Methods: This cross‐sectional study was performed with a total of 131 patients (62 women and 69 men, mean age 42.96±13.02 years). Patients were divided into three groups: UC, CD, and non‐IBD. Periodontal status was defined according to the 2017 World Workshop Disease Classification. Salivary and GCF cytokine levels were analyzed using ELISA. Results: UC and CD patients diagnosed as having periodontitis and gingivitis presented with significantly higher levels of TNF‐α and lower levels of IL‐10 as compared with non‐IBD patients ( p <0.05). UC patients diagnosed with periodontitis exhibited significantly higher scores of bleeding on probing ( p = 0.011) and increased salivary and GCF IL‐1β levels as compared with CD patients ( p = 0.005, and 0.012, respectively). Considering the active and remission status of IBD, salivary IL‐1β was found to be correlated with the parameters representing the severity of periodontal diseases in active UC and CD patients. Conclusion: In the presence of periodontal diseases, UC and CD patients showed different expression levels of TNF‐α, IL‐1β, and IL‐10 in oral secretions as compared with non‐IBD patients.